Between stories and stage: narrative presence in Samuel Beckett‘s dramatic art - Öztürk, Dilek. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
This study intends to analyze drama and narrative on Samuel Beckett‘s stage within the context of storytelling. Narrative theory is taken as a departure point here, for Beckett‘s drama with its actor-narrators, never-ending stories and idiosyncratic performances lends itself easily to storytelling. While storytelling as a familiar motif in Beckettian fiction has been widely discussed by many scholars, Beckett‘s drama within the context of narrative theory has not received much critical attention. This study tries to show how the two fields, narrative and drama meet at converging paths as one gets to explore narrative presence on Beckett‘s stage. Various stories on Beckett‘s stage, which are open-ended, self reflexive and fragmented, reshape our notion of "drama" and "narrative." As soon as one steps into Beckettland permeated by idiosyncratic narrations and performances, the line between narration and performance gets blurred. "Narrative" becomes "drama,"narrating" takes the place of "acting;" every single word, sound and silence on the stage forms the dramatic atmosphere of the play. At that moment, any particular talk, be it significant or insignificant, between the characters, comes to be perceived as the real dramatic action of the play.
Keywords: Narration (Rhetoric)